The Journeys of two Mindanao Ulama in the late eighteenth century to early nineteenth century - Kawashima, Midori (Journal of Philippine local history and heritage, 2017)
Although many studies have been conducted on the history of Muslims in the Philippines, a substantial study of the personalities, activities, and thoughts of individual ulama (Islamic scholars) from the southern Philippines before the twentieth century is conspicuously lacking. As a result, Muslims in Mindanao and Sulu before the U.S. colonial period are usually regarded as intellectually inactive. This study looks at their history in a new light, focusing on two ulama from Mindanao: 'Abd al-Majid al-Mindanawi, who wrote an Islamic manuscript in Aceh in the late eighteenth century, and Sayyidna Tuan Muhammad Said, who traveled from the Lake Lanao region of Mindanao to Mecca at the beginning of the nineteenth century. In discussing their journeys and achievements, this paper draws on the manuscripts written by these two intellectuals during their travels. Actively participating in intellectual interactions with fellow Muslims in the Malay world, both persons were firmly integrated in the network of ulama that connected the centers of Islamic learning in Southeast Asia with those in Middle East. Moreover, they were not only on the receiving end of foreign knowledge but were also actively engaged in transmitting and producing knowledge by writing manuscripts in Malay. Thus, this study challenges the prevailing narrative that describes the Philippine Muslims primarily as brave warriors and their history predominantly in terms of a series of battles to defend their land against foreign aggressors. Although such actions represented part of their experiences, the southern Philippines also produced Islamic scholars who contributed to the enrichment of Muslim intellectual and cultural life in their homeland as well as in the Malay world.